2007
DOI: 10.1128/jcm.01325-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cepheid's Analyte-Specific Reagents with BD Directigen for Detection of Respiratory Syncytial Virus

Abstract: For detection of respiratory syncytial virus (RSV), the BD Directigen RSV rapid antigen assay was compared to Cepheid's real-time reverse transcriptase PCR RSV analyte-specific reagents. The Directigen RSV assay resulted in a 23% false-negative rate, using PCR and chart review as the gold standard, indicating that rapid RSV PCR results would be advantageous.Rapid detection of respiratory viruses is important for many reasons, including prevention of unnecessary antibiotic use, identification of individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The improved sensitivity of PCR over antigen testing and virus isolation for RSV (14,16,44,45) and influenza virus (17,20,40,41,48) has been previously demonstrated by uniplex, as well as multiplex, testing (4,23,28,32). Studies have also demonstrated improved sensitivity of PCR in combination with culture as a composite "gold standard" or as the alternate reference test for RSV or influenza virus (1,19,33,36,38).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The improved sensitivity of PCR over antigen testing and virus isolation for RSV (14,16,44,45) and influenza virus (17,20,40,41,48) has been previously demonstrated by uniplex, as well as multiplex, testing (4,23,28,32). Studies have also demonstrated improved sensitivity of PCR in combination with culture as a composite "gold standard" or as the alternate reference test for RSV or influenza virus (1,19,33,36,38).…”
Section: Resultsmentioning
confidence: 82%
“…Studies have also demonstrated improved sensitivity of PCR in combination with culture as a composite "gold standard" or as the alternate reference test for RSV or influenza virus (1,19,33,36,38). A very small minority of previous studies evaluating PCR detection of influenza virus and RSV have included controls to monitor inhibition due to inadequate extraction and purification of nucleic acids (16,23,28,36). Estimates of sensitivity are incomplete or compromised without the inclusion of an internal control to monitor these potential false-negative results.…”
Section: Resultsmentioning
confidence: 99%
“…To date, one of the most sensitive diagnostics available for the detection of RSV has been the use of Reverse Transcription Polymerase Chain Reaction (RTPCR) to amplify and detect RSV genetic material [19] and [20]. However, detection of the negative-sense RNA genome or mRNA of the virus comes with a few drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…However it is not feasible to provide urgent out of hours testing based on this multiplex format therefore alternative virus specific testing is preferable for urgent individual samples. A rapid, real-time PCR-based diagnostic test for RSV and influenza A and B which can be performed in a relatively short turn around time would be extremely useful for patient management (Goodrich and Miller, 2007). In addition, the resulting improved treatment of patients presenting with respiratory illness would help infection 0166-0934/$ -see front matter © 2009 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%